Design of an automatic drinking water filling system using an IoT-based microcontroller for SME - P. Paryanto; Pungki I. Laksana; R Rusnaldy; Bambang Riznanto; Heru Kustanto; Gustri Yeni (Institution for Industrial Research and Standardization of Industry - Padang, 2022)
Beverages and other commodities packaged in bottles for small and medium industries (SMEs) generally require a relatively long production time. This process is significantly dependent on the workers' skills to achieve higher production costs and low efficiency. Therefore, this research designed an automated water-filling device for improving and monitoring SMEs productivity in real-time. The system comprises four types of sensors, namely ultrasonic, temperature, TDS (total dissolved solids), and proximity. The ultrasonic and temperature sensors measure the water level and temperature in the holding tank. The TDS sensor measures the value of substances or particles dissolved in the water, while the proximity sensor detects and counts the number of bottles. Sensor readings are displayed on the LCD (liquid crystal display) and can be monitored via a smartphone using the Blynk application. In conclusion, the existing automation system accompanied by an IoT-based monitoring system can help SMEs to check the quality and efficiency of production in real-time.